Anionic water-soluble sulfonated phthalocyanines: microwave-assisted synthesis, aggregation behaviours, electrochemical and in-situ spectroelectrochemical characterisation - KOCA, ATIF (TAYLOR & FRANCIS LTD, 2017)
In this work, a phthalonitrile derivative bearing p-sulfonylphenoxy group at the 3-position has been synthesised. The water-soluble non-peripherally tetrasubstituted zinc (3) and cobalt (4) phthalocyanines were obtained by cyclotetramerisation of this phthalonitrile derivative in the presence of anhydrous metal salts by microwave irradiation. The compounds have been characterised by using FT-IR, H-1 NMR, UV-Vis and Mass spectrometry (MS) data. The aggregation behaviours of these compounds were investigated in methanol, DMSO, DMF, and water. We have also studied the aggregation behaviours of the phthalocyanine complex 3 in various DMSO/water mixtures. Additionally, the redox properties of the phthalocyanine complexes were examined in dimethylsulfoxide by voltammetry and in situ spectroelectrochemistry. Redox behaviours of the complexes supported the structures of the complexes. Metal and ring-based reductions were observed for 4 and only ring-based electron transfer processes were observed with 3.
Keywords: Sulfonated phthalocyanines; anionic; water-soluble; non-peripheral; aggregation; spectroelectrochemistry; SUBSTITUTED PHTHALOCYANINES; ZINC PHTHALOCYANINE; PHOTODYNAMIC THERAPY; SINGLET OXYGEN; METAL-FREE; METALLOPHTHALOCYANINES; INACTIVATION; SENSITIZERS; SEPARATION; ISOMERS